Alice Dunbar-Nelson, Zora Neale Hurston, and the Creation of "Authentic Voices" in the Black Women's Literary Tradition - (:unkn) unknown (My University, 2016)
This dissertation focuses on African American women’s literature from the 1890s through 1948, covering the New Negro movement and sentimental domestic novel, the folk writings of the early twentieth century, and white-life fiction. The study investigates writers and texts that at various points in the creation of a black women’s literary tradition have been labeled “inauthentic” or have otherwise received comparably little attention by scholars of the tradition. In particular, I examine the work of Alice Dunbar-Nelson and Zora Neale Hurston, placing them in conversation with one another and within the broader context of black women’s writing at the turn of the twentieth century. Dunbar-Nelson’s work is only beginning to be recovered by scholars; most of the recent criticism of her texts is intent on proving that she was engaged in discussions of racial politics, rather than considering how or why she wrote fiction that differed so greatly from her contemporaries. I consider how her regional fiction expands on and revises the work of earlier writers such as Frances E. W. Harper and Pauline Hopkins, especially their portrayals of New Negro Womanhood. I argue that Dunbar-Nelson uses the genres of regional and white-life fiction to critique uplift narratives and Victorian social conventions, common in earlier texts, and instead forecasts the root black identification in Southern culture that we find in Hurston’s writing. I compare Hurston’s less-frequently studied short stories and white-life fiction to Dunbar-Nelson’s, drawing attention to the similarity of their use of folklore as well as their politics more generally. Ultimately, I argue that Dunbar-Nelson’s writing needs to be considered in context with writers already considered members of the black women’s literary tradition, both as a part of her recovery and in an effort to interrogate the boundaries of that tradition. Literary traditions, I maintain, are constructed not only by the authors in them, but by the critics who create them; constructions though they may be, they are nevertheless necessary acts of critical resistance that must be continually examined and revised.